1999
DOI: 10.1016/s0741-5214(99)70203-x
|View full text |Cite
|
Sign up to set email alerts
|

The role of heparin-associated antiplatelet antibodies in the outcome of arterial reconstruction

Abstract: The frequent exposure to heparin by patients with peripheral vascular disease is associated with a high incidence rate (21%) of HAAb formation, which makes it one of the more common hypercoagulable conditions in these patients. The patients who were HAAb positive had a 2.6-fold increase in perioperative thrombotic events. Thrombocytopenia or decreasing platelet counts were not reliable clinical markers for identifying patients who were HAAb positive. It is suggested that all patients who have undergone heparin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 26 publications
1
18
0
Order By: Relevance
“…In addition to mediating HIT, heparin-PF4 antibodies are independent predictors of adverse outcomes in various patient populations, particularly cardiac and cardiovascular surgery patients [5][6][7][8][9][10][11][12], and some experts suggest including heparin-PF4 antibodies in the preoperative cardiac surgery risk profile [9]. We observed in medical, neurotrauma, or shock-trauma ICU patients that the median durations of ICU stay and hospital stay were greater in seropositive patients than seronegative patients, which is suggestive of a possible effect, yet few thrombotic or fatal events occurred overall.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to mediating HIT, heparin-PF4 antibodies are independent predictors of adverse outcomes in various patient populations, particularly cardiac and cardiovascular surgery patients [5][6][7][8][9][10][11][12], and some experts suggest including heparin-PF4 antibodies in the preoperative cardiac surgery risk profile [9]. We observed in medical, neurotrauma, or shock-trauma ICU patients that the median durations of ICU stay and hospital stay were greater in seropositive patients than seronegative patients, which is suggestive of a possible effect, yet few thrombotic or fatal events occurred overall.…”
Section: Discussionmentioning
confidence: 99%
“…The recommended treatment for HIT is to stop heparin immediately and initiate fast-acting, nonheparin anticoagulation [3,4]. Even in the absence of thrombocytopenia, heparin-PF4 antibody seropositivity is associated with increased thrombotic risk, length of hospitalization, or mortality in cardiac [5,6], cardiovascular surgery [7][8][9], orthopedic surgery [10], hemodialysis [11], and pediatric intensive care unit (ICU) patients [12]. Antibody-associated endothelial cell activation may play a role in the pathophysiology of these effects [13].…”
Section: Introductionmentioning
confidence: 99%
“…In regard to disease specific impacts on HIT, comprehensive and reliable data mainly exist based on patient series from cardiac surgery [17] , orthopedic surgery [18] , and vascular surgery [19,20] . However, reports and systematic studies on HIT in solid organ transplant recipients are rare and inconclusive.…”
Section: Introductionmentioning
confidence: 99%
“…1,28 The presence of heparin-PF4 antibodies, especially in high titers and irrespective of the presence of thrombocytopenia or thrombosis, is associated with increased all-cause mortality and morbidity in a number of patient populations. 3,29 Studies have reported significantly higher hospital mortality rates after cardiac surgery 30 and a higher incidence of thrombotic events in vascular reconstruction 31 and orthopedic surgery patients. 20…”
Section: Epidemiology and Risk Factors For Hitmentioning
confidence: 99%